The traveller from the heavens - Khan ,Nafees (Goodword Books: New Delhi, 2010)
The book presents this profound event in a child-friendly manner, using colorful illustrations and engaging rhymes to make the story accessible and enjoyable for young minds. By blending educational content with fun storytelling, it aims to instill an early understanding of Islamic teachings and the significance of Gabriel's visit in a way that's both informative and entertaining.